2019
DOI: 10.1002/pat.4744
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of bismuth oxide and mono‐component intumescent flame retardant on the flammability and smoke suppression properties of epoxy resins

Abstract: A novel mono‐component intumescent flame retardant named pentaerythritol phosphate melamine salt (PPMS)‐hybrid bismuth oxide (PPMS‐Bi2O3) was synthesized and carefully characterized by FTIR, 1H NMR, 31P NMR, SEM‐EDS, and TG analyses. Then, PPMS‐Bi2O3 was utilized as flame retardant for epoxy resins (EPs), and the thermal stability, flame retardancy, and smoke suppression properties of EP composites were investigated. TG results show that PPMS‐Bi2O3 is more conducive to enhance the thermal stability and char fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For epoxy resin, intumescent flame retardant systems have also attracted the attention of researchers. [19][20][21][22] Chen et al 23 26 Therefore, a high addition of IFR is often inevitable to acquire the desired flame retardant properties, which needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For epoxy resin, intumescent flame retardant systems have also attracted the attention of researchers. [19][20][21][22] Chen et al 23 26 Therefore, a high addition of IFR is often inevitable to acquire the desired flame retardant properties, which needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of charring agents, such as hyperbranched polyamines containing triazines, 13 hyperbranched polyamine carbonation agent (HPCA), 14 semi‐bio‐based synergist (TTG), 15 molecule containing phosphazene and triazine groups (HTTPC), 16 polyhydroxy triazine‐based charring agent (TTPC), 17 organic‐inorganic hybrid char‐forming agent (SCTCFA‐ZnO) based on triazine groups 18 and so on, have been prepared and applied in polymer materials, especially polyolefin, which presented better fire performance than generally used traditional agents. For epoxy resin, intumescent flame retardant systems have also attracted the attention of researchers 19‐22 . Chen et al 23 prepared monocomponent intumescent flame‐retardant EP composites based on an organic‐inorganic hybrid (EDA‐APP), and UL‐94V‐0 was reached with 16.3 wt% EDA‐APP via adding extra 1.7 wt% Cu 2 O. Jian et al 24 synthesized a benzothiazole‐based phosphamide (DOP‐ABZ) and EP/20 wt% DOP‐ABZ could passed UL‐94V‐0 rating with a LOI value of 28.3%.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Xu et al showed that the chemical combination of Bi 2 O 3 and pentaerythritol phosphate melamine salt exhibits a strong catalytic effect on charring effect of EPs, thus significantly reducing the generation of heat and smoke. [23] Apart from metal oxides, layered silicates, such as organically modified montmorillonite (OMMT), are also as high-efficient synergists for intumescent system, and the synergistic effect is mainly ascribed to the formation of carbonaceous-silicate structures that act as an effective physical protective barrier on the surface of the material against the heat and mass transfer during combustion. [24][25][26] Yan et al found that the addition of OMMT is beneficial to enhance the compactness and continuous of the intumescent char, showing an obvious synergistic effect in transparent intumescent fire-retardant coatings.…”
Section: Introductionmentioning
confidence: 99%
“…EP is a kind of multi-purpose resin that is widely used in various industrial fields such as adhesives, transportation, aerospace, electronics, and composite materials [1][2][3]. However, the limiting oxygen index (LOI) of unmodified EP is only 19.8%, accompanied by more severe smoke during the burning process [4][5][6]. This defect seriously hinders EP's development and application [7].…”
Section: Introductionmentioning
confidence: 99%